ANALISIS KESIAPAN PELAKSANAAN SOSIALISASI PROGRAM AMBULANCE HEBAT DALAM RANGKA DUKUNGAN TERHADAP SISTEM PENANGGULANGAN GAWAT DARURAT TERPADU DI KOTA SEMARANG - Wiwid Novitaria; Putri Asmita Wigati; Ayun Sriatmi (Jurnal Kesehatan Masyarakat (Undip), 2017)
An integrated emergency response system is planned action undertaken by the Ministry of Health of the Republic of Indonesia in preventing casualties caused by the emergency, one of them is traffic accidents. The City Government of Semarang established a program called Ambulance Hebat as an emergency service based call center in Semarang City. Health Office of Semarang City conducted socialization for the community and stakeholders so that the program can be used optimally, but not all people know about the Ambulance Hebat program.Therefore, it is necessary to analyze the implementation readiness of the integrated emergency response system in the socialization aspect in the pre-hospital phase (Case study: Traffic accident in Semarang City).This research was conducted using qualitative research method by using purposive sampling technique which then continued by deep interview with research informant.Based on the result of the research, it is know that the information received by the people is not as complete as it was delivered at the beginning of socialization. The misinformation caused many people not fully understand the functions of the Ambulance Hebat program, and many even did not know such program is exist. In addition, the number of case reporting in each Puskesmas area that became a network of Ambulance Hebat is also unequal.There is one area with the most reporting cases asnd there are also areas with absolutely zero reports cases at all. It indicates that the socialization has not been equal and the information delivered has not been delivered properly. The result of analysis conducted in this research study suggests the Health Office of Semarang City to start monitoring the delivery of information from the beginning until it passed to the people.